(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This paper proposes a conceptual and algorithmic model of an AI-driven interactive televised debate platform adapted for Uzbekistan’s political information landscape. Through a combination of surveys, content analysis, and mathematical modeling, the study assesses the communicative efficiency of classical debate formats. The findings indicate limited audience engagement in traditional formats, while the integration of artificial intelligence significantly enhances interactivity through tools such as fact-checking, sentiment analysis, and real-time participation. A mathematical model based on user response metrics and temporal dynamics is introduced to simulate algorithmic interaction in political discourse. The proposed platform aims to foster transparency, public trust, and digital civic engagement.